Echinoderms Diversity and Abundance in Gunung Kidul Beach Yogyakarta - Supriyati, Hikmah; K, Setyawati Dwi; Ahzami, Ahzami; Sodiq, Farhani; Khoiriyah, Septiana (Biology, Medicine, & Natural Product Chemistry, 2019)
Echinoderms are one of marine invertebrate animals that have an important role, as a recycle of nutrients in the functioning of ecosystems. Echinoderms usually appear in the intertidal zone of the coast. The existence of echinoderms in the intertidal zone is affected by external and internal factors. This study aims to determine the level of abundance and diversity of Echinoderms in the intertidal zone in the Krakal and Drini coastal areas, Gunung Kidul, Yogyakarta. Data were collected using transect method. The main transect along 50 meters was divided into 5 sampling points, and the distance between sampling points was 10 meters. After that, each point was taken for 3 observation plots with an area of 1x1 meters and the distance between plots is 5 meters. The results showed that, the diversity index on the krakal coast had a higher value (0.139) when compared to the Drini coast (0.129). Calculation of echinonderm abundance index shows that the Drini beach location has a high abundance value when compared to the abundance value at the Krakal beach loc ation. The parameter measurement results can be seen that both the pH and temperature parameters on both the Krakal and Drini coast have values that correspond to the optimum parameter in the waters.